1987
DOI: 10.1007/bf00177918
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of the stimulant and depressant effects of ethanol in rats by naloxone

Abstract: The action of naloxone (0.5 and 2 mg/kg IP) on the behavioural effects of a low (2 g/kg PO) and a high dose (4 g/kg PO) of ethanol was studied in rats. Ethanol at the low dose increased spontaneous motility, enhancing open-field external ambulations and reducing shuttle-box latency. All these effects were antagonized by naloxone. Ethanol at the high dose produced by hypomotility, decreasing open-field external ambulations and impairing shuttle-box performance. In this case, naloxone also reduced the ethanol ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…There was evidence of a small locomotor stimulant effect of 30-minute immersion in 0.1 M EtOH as reflected in a significant increase in Center speed. This is consistent with observations in the rat in which lower doses produce locomotor stimulation while higher doses suppress activity (Prunell et al, 1987). There was no indication of a more robust stimulant effect of 0.05 M immersion, see Supplemental Figure S5 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was evidence of a small locomotor stimulant effect of 30-minute immersion in 0.1 M EtOH as reflected in a significant increase in Center speed. This is consistent with observations in the rat in which lower doses produce locomotor stimulation while higher doses suppress activity (Prunell et al, 1987). There was no indication of a more robust stimulant effect of 0.05 M immersion, see Supplemental Figure S5 .…”
Section: Discussionsupporting
confidence: 92%
“…It was found that 2 g/kg, p.o. increases activity in rats, whereas 4 g/kg was reported to decrease activity (Prunell et al, 1987). Similarly 2 g/kg EtOH, i.p., decreased motor activity in 20, 40 or 60 day old rats (Lamble and Rydberg, 1982) and 0.75 g/kg, i.p.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that naloxone prevented the improving effect of ethanol on memory recall. According to Prunell et al (1987) both the CNS stimulant and depressant effects of ethanol in rats have been antagonized by naloxone. However, other investigators suggested that the effects of naloxone are probably due to a non-specific analeptic action rather than blockade of opioid receptors (Saddler et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Though the particular alleles and gene products contributing to EtOH induced locomotor changes remain obscure (Phillips et al, 1995), opioid peptides have been implicated (Prunell et al, 1987; Kuribara et al, 1991; Sanchis-Segura and Aragon, 2002; Sanchis-Segura et al, 2005). In this study we evaluated the effect of β-E on the development of locomotor sensitization to repeated EtOH exposure using transgenic mice that vary in their capacity to synthesize the peptide.…”
Section: Introductionmentioning
confidence: 99%